Collectors and collecting for the Raffles Museum in Singapore : 1920 to 1940 - Luyt, Brendan (2010)
The study of museums as part of society has been underway for some time now and a number of pioneering and insightful works have been written on their changing nature and role [1]. I would like in this article to add to this body of literature through the example of one museum director’s efforts at expanding the collection of his institution (the Raffles Museum in Singapore) in the 1920s and 1930s. In particular, I wish to show how the social relationships that make much collecting possible are structured around the exchange of tangible and non-tangible resources. Given that much of the literature on museums tends to reflect the experiences of the imperial or white settler societies (UK, USA, Canada, Australia, and New Zealand), my focus on the Raffles Museum has the added benefit of exploring an under-examined geographical area [2].